Geotechnical zonation and bearing capacity assessment for risk-informed foundation design in the heterogeneous soils of Girsang Sipangan Bolon, Indonesia - Nata, Refky Adi; Ren, Gaofeng; Andas, Jukepsa; Yulanda, Yudi Arista; Rahmi, Hisni; Syahmer, Verra (Journal of Degraded and Mining Lands Management, 2026)
Subsurface?failures, often caused by poor site investigation, are a serious issue in geotechnical engineering. This research focused on unpredictable soil response at a geologically complex site in Girsang Sipangan Bolon District, Indonesia, where very high significant variation in subsoil conditions led to foundation failure. The subsurface profile was studied, and the ultimate bearing capacity (UBC) was first characterized in this research for safe foundation design. The site investigation utilized 11 boreholes, including Standard Penetration Tests (SPTs) and undisturbed sampling. They processed the readings using Meyerhof's theory and determined the UBC for strip, pad, and circular foundations. The findings showed extremely high subsurface heterogeneity (with SPT-N values between very soft top layers and ultra-dense rock-coral). Therefore, there?is a large variation in the predicted UBC. Based on statistical analysis of the data, clear geotechnical zones were defined, with some boreholes showing high, consistent capacity and others showing locally weak strata. Fill and ring foundations also had greater theoretical bearing?capacities than rectangular footings. The main conclusion is that?sufficiently pronounced subsurface heterogeneity requires site-specific geotechnical investigations to minimize the risk of differential settlement. Therefore, foundation design cannot be uniform throughout the site; deep foundations, such as end-bearing piles, are suggested in highly variable zones to transfer loads to competent strata and ensure long-term structural safety.